Penerapan Metode Simple Addictive Weighting (SAW), Metode Weighted Product (WP), Dan Technique for Order Preference By Similarity To Ideal Solution (TOPSIS), Dalam Pemberian Bonus Tahunan Karyawan - Rio Ardy Milala; Ahmad Fajri; Moh.Ridzki Alif Maulana; Nazila Iva Sugianisa; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Granting annual bonuses to employees Improving staff morale and performance is one method of improving both within the Financial and Asset Management Agency. However, there are a number of factors that are taken into account when annual incentives are awarded. In order for us to select the best staff, we need a decision aid system. In this research, three techniques are chosen. namely SAW (Simple Additive Weighting), Weighted Product (WP) Method, And Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) This is achieved by assigning importance to each standard evaluated for each employee. Workload, attendance rate, discipline, and other factors are also considered when evaluating research parameters and salary requests. The final result is the selection of the best employee who obtains the largest score deserves the largest bonus.